2018
DOI: 10.4028/www.scientific.net/msf.918.159
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Tooling Design for Hot Mandrel Bending of Pipe Elbows

Abstract: This paper presents the finite element model developed for the simulation of pipe elbow production by the so-called ‘Hamburg process’ in order to improve productivity and resource efficiency. To optimize the tooling design, a sensitivity analysis of the tool parameters that influence the quality of pipe elbows, such as mandrel height and length, is conducted. Different materials data sets including damage models were considered. Using numerical simulations, it is possible to determine an optimized tool geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Oh et al [10] examined the influence of tube blank shape on forming quality, but they did not explore the influence of process parameters on forming quality. Tabakajew and Homberg and Diekmann et al [11,12] discussed the influence of mandrel size on the quality of elbows. Guo et al [13] described the influence of three types of mandrels on the forming quality of an L-shaped elbow.…”
Section: State Of the Artmentioning
confidence: 99%
“…Oh et al [10] examined the influence of tube blank shape on forming quality, but they did not explore the influence of process parameters on forming quality. Tabakajew and Homberg and Diekmann et al [11,12] discussed the influence of mandrel size on the quality of elbows. Guo et al [13] described the influence of three types of mandrels on the forming quality of an L-shaped elbow.…”
Section: State Of the Artmentioning
confidence: 99%
“…At present, this process has been widely used in the production of transportation pipelines and metal structure parts. Plentiful studies are reported on this process by theoretical analysis, experimental research and numerical simulation [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%